Physician practices and attitudes towards atopic dermatitis in Latin America: A cross- sectional study (2023)
Background: The prevalence of atopic dermatitis (AD) is increasing in developing countries. Different worldwide guidelines have been proposed, but their applicability for AD specialists in Latin American (LA) countries is unknown. Objective: The objective of this study was to explore the medical approach to treating AD in LA countries. Methods: The study population comprised AD specialists (allergists and dermatologists). They completed an electronic survey containing questions about the health system, diagnostic criteria, and pharmacotherapy approach to treating AD. The survey was constructed and validated by the Atopic Dermatitis Committee of the Latin American Society of Allergy Asthma and Immunology (SLAAI) in Spanish and Portuguese. Each member was responsible for distributing the questionnaire through different networks in their respective countries. Results: A total of 284 AD specialists from 13 LA countries completed the questionnaire; among them, 67% were allergists and 33% were dermatologists. Less than 50% of the AD specialists strictly followed guideline recommendations. Among the AD specialists, the European and North American guidelines were more frequently used, and only 16% followed LA guidelines. Dermatologists used the local guidelines less frequently than allergists. Most physicians did not routinely use AD assessment tools (55%). The frequency of the diagnostic tests depends on symptom severity. The availability of some systemic treatments, such as biologics and Janus Kinase (JAK) inhibitors, is not universal in all LA countries. Conclusion: There were marked differences between the specialists, and these differences seemed to be affected by their specialty and each country's healthcare system. New AD education strategies that consider the particularities of the region could allow patients to be more accurately managed. AD assessment tools may provide a way to enhance AD treatment and allow for shared decision-making, patient empowerment, and standardized care.